Drug repositioning for pan-cancers of the digestive system: Identification of amonafide and BX795 as potential therapeutics via integrative Omics analysis - Weidong Liu; Jiaying Gao; Shuqiang Ren; Buhe Nashun; Fei Gao (PLoS ONE, 2025)
Background Digestive system cancers, including esophageal, gastric, colorectal, pancreatic, hepatocellular, and biliary tract cancers, constitute a major global health challenge. Despite therapeutic advancements, prognosis remains poor, highlighting the urgent need for novel treatment strategies. We hypothesized that drug repositioning, facilitated by pan-cancer analyses, could lead to the identification of effective treatment strategies for these cancers. Results We performed a comprehensive gene expression profiling of six major digestive system cancer types using The Cancer Genome Atlas data. Through integrative omics analysis, we identified 9,978 shared differentially expressed genes (DEGs) between colorectal cancer (CRC) and liver hepatocellular carcinoma (LIHC). Functional enrichment analysis revealed nine common Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, with Cell Cycle being a significant shared pathway. Protein-protein interaction (PPI) network analysis identified core genes within these pathways, including CCNE1, CHEK1, NXF1, NCBP2, and RPS27A. A Connectivity Map (CMap) analysis matched 1,147 small molecules, leading to the identification of Amonafide and BX795 as top candidates. These two drugs were validated and shown to inhibit the proliferation and migration of CRC (HT-29) and LIHC (HepG2) cells and induce cell cycle arrest and apoptosis. Conclusion Our study demonstrates the utility of drug repositioning for identifying potential therapeutics for digestive system cancers. Amonafide and BX795 emerged as promising candidates in targeting both CRC and LIHC. Further in vivo studies and clinical trials are warranted to validate these findings.